2005
DOI: 10.1038/labinvest.3700305
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter felis-induced gastritis was suppressed in mice overexpressing thioredoxin-1

Abstract: Thioredoxin-1 (TRX-1) is a redox-active protein involved in scavenging reactive oxygen species and regulating redox-sensitive transcription factors. TRX-1 is induced in various inflammatory conditions and shows cytoprotective action. We investigated the roles of TRX-1 in the host defense mechanism against Helicobacter felis (H. felis) infection. Transgenic (TG) mice overexpressing human TRX-1 and wild-type (WT) mice were orally inoculated with H. felis. After 2 months, histology, oxidative damage, and gene exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 49 publications
2
12
0
Order By: Relevance
“…Thus, the loss of Ikkβ resulted in increased oxidative stress, DNA damage and cellular necrosis. Oxidative stress induced by ROS has an important role in the formation of gastric injury by Helicobacter infection 32. 18 months post H. felis infection, the gastric mucosa of Ikkβ Δstom mice also exhibited a higher number of anti-8-OHdG-positive cells than Ikkβ F/F mice (Figure 6 B ), suggesting that loss of Ikkβ is likely associated with the ROS accumulation and subsequent DNA damage in this model.…”
Section: Resultsmentioning
confidence: 91%
“…Thus, the loss of Ikkβ resulted in increased oxidative stress, DNA damage and cellular necrosis. Oxidative stress induced by ROS has an important role in the formation of gastric injury by Helicobacter infection 32. 18 months post H. felis infection, the gastric mucosa of Ikkβ Δstom mice also exhibited a higher number of anti-8-OHdG-positive cells than Ikkβ F/F mice (Figure 6 B ), suggesting that loss of Ikkβ is likely associated with the ROS accumulation and subsequent DNA damage in this model.…”
Section: Resultsmentioning
confidence: 91%
“…Nevertheless, it is noteworthy that administration of TRX during allergen-challenging phase, but not allergen-sensitization phase, suppressed airway inflammation, indicating that TRX could suppress Th2-driven inflammation irrespectively of initial development of Th2 immunity [23]. When all of the data are considered together, there are a number of studies that demonstrated a protective role for endogenous and/or exogenous TRX in different models of inflammatory diseases including autoimmune myocarditis [34], diabetes [18,35], gastritis [36], colitis [32] as well as asthma [23,37]. Thus, it seems unlikely that the sole function of TRX to negatively regulate inflammatory reactions is mediated through the modulation of Th1/Th2 immunity.…”
Section: Discussionmentioning
confidence: 99%
“…TRX-1 shows cytoprotective action in various inflammatory conditions. For example, TRX-1 reduces DNA damage and neutrophil aggregation in the Helicobacter felis-infected stomach, suggesting a protective role in murine gastritis (144).…”
Section: Thioredoxinmentioning
confidence: 99%